Clinical experience with technetium-99m stannous polyphosphate for myocardial imaging. - Gould, L A (1976)
Myocardial imaging with technetium-99m stannous polyphosphate was performed on 46 patients. Eleven patients had no cardiac disease, 22 had acute myocardial infarction, and 13 had stable arteriosclerotic heart disease. Distinct patterns of myocardial activity were noted: (1) the patients with no obvious cardiac disease showed no cardiac activity; (2) stable arteriosclerotic heart disease showed faint, ill-defined cardiac activity, primarily in the anterior or inferior aspect of the left ventricle; (3) acute myocardial infarction showed intense, focal, well-defined activity, with a shape that characterized the location of the infarct.